ENUJU REPOSISI PERAN INTERNAL AUDIT DALAM ERA GLOBALISASI - Hery (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
In the global era, it iis very important for a company to develop continuously a contemporary mnagement accounting technic that could hel achieve company's success factors (such as pmfitability customer satisfaction, etc). Some factors that generate changes in contemporary business environment are market growth and international trading.Much changes in the business environment for the past few year, had make the role of internal consultant will be needed in helping management to face and to win the global competitive. It is time for intemal auditor as a management consultant to expad their role, in manner to give strategic information and prime service for management. This role doesn't restrict on internal chekig only. Internal auditor have to perform fully their role and dute as an internal consultant. Internal consultant is highest expression in the role of internal auditor.Kata Kunci : Inte4nal audit, the global era, re-position of the role.